Academic Staff Mobility in the Age of Trump and Brexit? - Leisyte, Liudvika; Rose, Anna-Lena (International Higher Education, 2017)
In times of increasing populism, nationalist tendencies, and strong public anti-immigration discourses, traditional patterns of international academic staff mobility come under question. Could this provide new opportunities for previously more disadvantaged, peripheral systems of higher education?